Review of the horse flies of the genus Atylotus Osten Sacken, 1876 (Diptera: Tabanidae) from Egypt, with description of a new species - El-Hassan, Gawhara M. M. Abu; Badrawy, Haitham B. M.; Fadl, Hassan H.; Mohammad, Salwa K. (Zootaxa, 2019)
The genus Atylotus Osten Sacken in Egypt is revised. A new species Atylotus shagrensis sp. nov. is described collected from Wadi Shagra (Eastern Desert). A key to species with illustrations is provided. Diagnosis, specimens examined and distributions are given for each species.